2013
DOI: 10.1016/j.eururo.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Volume–Outcome Relationship for Radical Prostatectomy

Abstract: Context Due to the complexity and challenging nature of radical prostatectomy (RP), it seems reasonable to suppose that both short- and long-term outcomes strongly depend on the cumulative number of cases performed by the surgeon as well as within the hospital. Objective To review systematically the association between hospital and surgeon volume and perioperative, oncologic, and functional outcomes after RP. Evidence acquisition A systematic review of the literature was performed, searching PubMed, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 86 publications
(124 reference statements)
9
125
0
5
Order By: Relevance
“…In addition, most observational studies generally include men treated at high-volume tertiary referral centers. Since surgeon, radiotherapist, and oncology expertise, as well as hospital case volumes, affect treatment-related outcomes [18][19][20][21], results obtained in this setting might not be applicable to the general population. Unlike the majority of cancer data sets from large, highly specialized, singlecenter academic or tertiary referral institutions in the USA and Europe, registries reflect outcomes in men with PCa treated in real-world community settings.…”
Section: A Role For Pca Registriesmentioning
confidence: 99%
“…In addition, most observational studies generally include men treated at high-volume tertiary referral centers. Since surgeon, radiotherapist, and oncology expertise, as well as hospital case volumes, affect treatment-related outcomes [18][19][20][21], results obtained in this setting might not be applicable to the general population. Unlike the majority of cancer data sets from large, highly specialized, singlecenter academic or tertiary referral institutions in the USA and Europe, registries reflect outcomes in men with PCa treated in real-world community settings.…”
Section: A Role For Pca Registriesmentioning
confidence: 99%
“…[1][2][3] Several studies have demonstrated a relationship between surgeon experience and outcomes in minimally-invasive prostate surgery. 4,5 Discrepancies in patient outcomes also lie in the hospital characteristics, with high-volume and teaching hospitals providing better quality care. 6,7 An integral aspect of surgical care in teaching hospitals is resident involvement.…”
Section: Introductionmentioning
confidence: 99%
“…This practice may reflect the US trends in expectant management utilization for prostate cancer ongoing centralization of American health care, with fewer RPs being performed on average at low-volume hospitals. 28,29 Urologists at these low-volume hospitals may prefer nonoperative management to RP.…”
Section: Discussionmentioning
confidence: 99%